2021
DOI: 10.3390/agriculture11121278
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Pantoea with Rice Plants: As Friends or Foes?

Abstract: Pantoea species are gram-negative bacteria from the Enterobacteriaceae family, generally associated with plants, either as epiphytes or as pathogens. In the last decade, Pantoea species are being regarded as re-emerging pathogens that are the causal agents of various diseases in rice plants. Inherently, they are also known to be opportunistic plant symbionts having the capacity to enhance systemic resistance and increase the yield of rice plants. It is unclear how they can express both beneficial and pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
1
15
0
Order By: Relevance
“…Different P. ananatis strains have diverse effects on maize seeds, ranging from weakly pathogenic to beneficial and growth-promoting effects ( Sheibani-Tezerji et al, 2015 ). Interestingly, the pathogenesis of P. ananatis appears to be strain-specific ( Kim et al, 2012 ; Doni et al, 2021 ). Our P. ananatis isolate did not show any pathogenic symptoms in rice seedlings and adult plants.…”
Section: Discussionmentioning
confidence: 99%
“…Different P. ananatis strains have diverse effects on maize seeds, ranging from weakly pathogenic to beneficial and growth-promoting effects ( Sheibani-Tezerji et al, 2015 ). Interestingly, the pathogenesis of P. ananatis appears to be strain-specific ( Kim et al, 2012 ; Doni et al, 2021 ). Our P. ananatis isolate did not show any pathogenic symptoms in rice seedlings and adult plants.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that this microorganism is useful as a biocontrol agent for black rot in sweet potatoes [27]. In addition, several members of the genus have been potentially found to enhance growth and yield, control plant pathogenic microbes, and increase abiotic tolerance in rice plants [28]. To our knowledge, this is the first report describing the isolation of bacterial species from healthy wood of Aquilaria crassna with rapid detection method.…”
Section: Sequence Analysis Of the 16s Rrna Gene And Phylogenetic Anal...mentioning
confidence: 99%
“…oryzae and Pantoea spp. is a major disease faced by rice growers in many countries, causing significant economic losses in rice yield world-wide, since the yield loss due to leaf blight can be more than 70% [ 16 , 130 ]. Over the years, many microbial inoculants have been evaluated as potential biocontrol agents against various bacterial diseases.…”
Section: Services Of Microbes In Protecting Rice Plants Against Plant Diseasesmentioning
confidence: 99%
“… Excessive use of biocides and chemical fertilizers resulted in the severe outbreaks of various rice diseases in Selangor, Malaysia: ( a ) Rice plants infected by Pantoea spp. with a yellowish leaf blight disease lesion on the leaves that leads to unfilled, empty, and discolored grains (photo courtesy of Muhammad Nazri Ishak), ( b ) Close-up view of the infected leaf with a lesion at the edge (adapted from Doni et al [ 16 ], the journal does not require permission to use materials), ( c ) Typical field symptoms of bacterial panicle blight caused by Burkholderia glumae with discoloration and sterility of grain as well as rotting and panicle blanking, ( d ) A close look at the severely infected panicle. The panicle remains upright rather than bending down with the weight of the grain (photo courtesy of Nurul Shamsinah Mohd Suhaimi).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation